X-Ray induced desorption and photochemistry in CO ice. Issue 30 (26th July 2021) - Dupuy, R.; Bertin, M.; Féraud, G.; Romanzin, C.; Putaud, T.; Philippe, L.; Michaut, X.; Jeseck, P.; Cimino, R.; Baglin, V.; Fillion, J.-H.
Abstract : We report an investigation of X-ray induced desorption of neutrals, cations and anions from CO ice. Abstract : We report an investigation of X-ray induced desorption of neutrals, cations and anions from CO ice. The desorption of neutral CO, by far the most abundant, is quantified and discussed within the context of its application to astrochemistry. The desorption of many different cations, including large cations up to the mass limit of the spectrometer, is observed. In contrast, the only desorbing anions detected are O − and C − . The desorption mechanisms of all these species are discussed with the aid of their photodesorption spectrum. The evolution of the X-ray absorption spectrum shows significant chemical modifications of the ice upon irradiation, which along with the desorption of large cations gives a new insight into X-ray induced photochemistry in CO ice.